2020
DOI: 10.1111/jcmm.16050
|View full text |Cite
|
Sign up to set email alerts
|

P21 activated kinase‐1 (PAK1) in macrophages is required for promotion of Th17 cell response during helminth infection

Abstract: The immune systems, which mainly consist of T cells, B cells and NK cells, are responsible for the maintaining of host homeostasis, adaptive immune responses providing protection against disease and specially infectious disease. 1 In particular, CD4 + T cells different subsets were essential for immune responses during host defence against pathogen infection and inflammatory diseases, 2-7 mainly including Th1, Th2, Th17 and Treg cells. The signals promoting differentiation of naive CD4 + T cells into a particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…PAK1 was shown to trigger the activation of inflammatory macrophages, thus inducing IL-6dependent TH17 differentiation and liver pathology in Schistosoma japonicum infection [94].…”
Section: Kinase Pathways Mediating Immune Regulatory Effects In Macro...mentioning
confidence: 99%
“…PAK1 was shown to trigger the activation of inflammatory macrophages, thus inducing IL-6dependent TH17 differentiation and liver pathology in Schistosoma japonicum infection [94].…”
Section: Kinase Pathways Mediating Immune Regulatory Effects In Macro...mentioning
confidence: 99%
“…P21-activated protein kinase (PAKs) had long been established to play important roles in vital cellular functions such as proliferation, survival and motility. Emerging evidence showed host PAK1 increased cell survival during the stage of virus infections [39], and recent study found PAK1 enhanced macrophage activation, resulting in promoting of Th17 cell response during Schistosoma japonicum infection [40], both of which guide the future research on the immunomodulation roles of host PAK1 and parasitic PAK1 in Fasciola infection. Camodulins (CaMs) were involved in fundamental processes including the phosphorylation of protein kinases, gene transcription and calcium transport [41].…”
Section: Discussionmentioning
confidence: 91%
“…P21-activated protein kinase (PAKs) had long been established to play important roles in vital cellular functions such as proliferation, survival, and motility (Arias-Romero and Chernoff 2008 ). Emerging evidence showed host PAK1 increased cell survival during the stage of virus infection (Van den Broeke et al 2010 ), and recent study found PAK1 enhanced macrophage activation, resulting in promoting of Th17 cell response during Schistosoma japonicum infection (Chang et al 2020 ), both of which guide the future research on the immunomodulation roles of host PAK1 and parasitic PAK1 in Fasciola infection. To further understand the functions of F. gigantica phosphoproteins annotated in more than 10 KEGG pathways, we took them in comparison with protozoa and helminths to identify possible connections between these phosphoproteins and biological processes of the parasites.…”
Section: Discussionmentioning
confidence: 97%